A Guide to Authorizing and Chartering 4-H Clubs or Affiliated Groups and Requirements for Tax-Exempt Status - Marilyn N. Norman; Joy C. Jordan (EDIS, 2008)
4-H 2.5, a 4-page fact sheet by Marilyn Norman and Joy Jordan, details the processes and requirements necessary to charter a 4-H Club or affiliated group and to obtain tax-exempt status for a 4-H club or affiliated organization. Published by the UF Department of Family, Youth and Community Sciences, January 2008.